An electronic companion to microbiology for majors. - Campbell Smith, Kathleen, ....-; Katz, Diana Sue, ....- (New York : Cogito Learning Media, 1997)
Contents: --------- 1. What are microorganisms? 2. Methods of microbiology 3. Prokaryotic cell structure 4. Eukaryotic cell structure 5. Growth and reproduction 6. Metabolism and energy 7. Microbial genetics 8. gene regulation 9. Classification 10. Viruses 11. Microbial ecology 12. Defense against infection 13. Disease
Keywords: Medische microbiologie; Microbiologie